Desenvolvimento de um curso on-line sobre anomalias craniofaciais para cirurgiões-dentistas - Cavalcante, Edilma da Cruz (2023)
The present study deals with the development, specifically construction and validation, of an online course, in the distance learning modality (DL), about the treatment of people with craniofacial anomalies for dental surgeons (DC) of Primary Health Care (PHC). The study used the ADDIE (analysis, design, development, implementation and evaluation) instructional design model, based on the theories of the Andragogical Model and the Heutagogical Model. It was developed in three stages. In the first, the didactic material was revised and updated. In the second, the course was built in the Online Learning System of the Federal University of Ceará (SOLAR-UFC). In the third stage the validity of the course was tested by six dentists with experience in craniofacial anomalies and/or educational technology. The course was evaluated using the adapted Emory Questionnaire for content, accuracy, audience and structure, and by another questionnaire on specific aspects of content and design. Overall, the course was rated as "excellent" or "adequate" by the evaluating judges. With regard to the Emory Questionnaire, the course was rated "excellent" with 96% agreement. The content, audience, and structure domains were rated "excellent" with percentages of 100%, 99%, and 100%, respectively. The accuracy domain was rated "adequate" with 89% percent agreement. As for the specific evaluation of content and design, 100% agreement was obtained by the content validity index (CVI), considering all items evaluated adequate. The online course reflected the needs pointed out in its conception, becoming a Permanent Education strategy apt to be made available. Besides facilitating the teaching-learning process and knowledge construction, it aims to improve the quality of care provided to people with craniofacial anomalies by PHC DC’s.